2007
DOI: 10.1677/joe-07-0427
|View full text |Cite
|
Sign up to set email alerts
|

The transcription of steroidogenic genes in the human cerebellum and hippocampus: a comparative survey of normal and Alzheimer's tissue

Abstract: Steroid actions on brain tissue have been implicated in processes such as blood pressure regulation and neurodegeneration, including the progression of Alzheimer's disease (AD). mRNAs from all of the genes required for de novo synthesis from cholesterol of aldosterone and corticosterone (equivalent to cortisol in humans) have been identified in rat brain, together with abundant steroid hormone receptors, but the situation in human brain requires clarification. We used real-time RT-PCR to assess whether transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…At least a marginal level of gene expression for most steroid synthetic enzymes has been detected using RT-PCR amplification of mRNA in tissue from various regions of the brain (67,68,115,116,190). The low-level expression of some of these enzymes may be regulated in the brain with some semblance to their counterparts in the adrenal gland (185,186).…”
Section: Other Brain Sites With Purported Aldosterone Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…At least a marginal level of gene expression for most steroid synthetic enzymes has been detected using RT-PCR amplification of mRNA in tissue from various regions of the brain (67,68,115,116,190). The low-level expression of some of these enzymes may be regulated in the brain with some semblance to their counterparts in the adrenal gland (185,186).…”
Section: Other Brain Sites With Purported Aldosterone Sensitivitymentioning
confidence: 99%
“…Third, there are major species differences in aldosterone synthase expression in the brain. One group found evidence for expression in rat, but not mouse, brain (165), and a more recent report failed to identify expression anywhere in the human brain (116). Fourth, and perhaps most importantly, the small amount of aldosterone detected in the brains of adrenal-intact animals rises and falls in direct proportion to plasma aldosterone, and little or no aldosterone can be detected in the brain after adrenalectomy (71,191).…”
Section: Other Brain Sites With Purported Aldosterone Sensitivitymentioning
confidence: 99%
“…However, although mRNA for other corticosteroidogenic genes has been detected in human brain samples, reverse transcription polymerase chain reaction (RT-PCR) studies have not found evidence of aldosterone synthase or 11β-hydroxylase gene transcription in human hippocampus or cerebellum [24,25]. Such differences prompt caution when drawing comparisons between the rat and human systems but do not necessarily mean that central corticosteroid synthesis is irrelevant to the human brain.…”
Section: Central Production Of Corticosteroidmentioning
confidence: 99%
“…Such differences prompt caution when drawing comparisons between the rat and human systems but do not necessarily mean that central corticosteroid synthesis is irrelevant to the human brain. First, the machinery does exist within the human hippocampus and cerebellum to produce 11-deoxycorticosterone (DOC), a steroid hormone capable of binding MRs, albeit with lower affi nity than aldosterone [25]. Second, rat studies point to another important cortico steroid-producing system within the paraventricular nucleus (PVN), and a corresponding system in this area of the human brain has not been ruled out.…”
Section: Central Production Of Corticosteroidmentioning
confidence: 99%
“…However, more subtle evidence suggests that deoxycorticosterone (DOC) might play direct roles on the hippocampus. First, DOC can be synthesized de novo in the hippocampus, implying the viability of local steroid effects (24). Second, hippocampal receptors for adrenal steroids are occupied and downregulated by systemic treatment with DOCA (22).…”
Section: Introduction: Hypertension and Brain Damagementioning
confidence: 99%